Perilaku Koruptif Dalam Praktik Manajemen Laba: Sebuah Tinjauan Perspektif “Ati Mapaccing” dalam Falsafah Bugis - Jumardi, Jumardi; Marina Palimbong, Stefani (Jurnal Ekonomi, Bisnis dan Terapan (JESIT), 2022)
Earnings management emerged in the field of financial accounting as a consequence of the efforts of managers or financial statement preparers to regulate the earnings cycle for personal and/or corporate interests or benefits. This study aims to gain an understanding of the opinions and behavior of informants including management accountants, public accountants, investment advisors, tax examiners and Bugis cultural observers on earnings management practices carried out by managers and viewed from the perspective of Classical Bugis philosophy. This type of research is a qualitative research with a hermeneutic approach, or more specifically an interpretive approach. Sources of data in this study are primary data and secondary data. Data collection techniques used in this research are interviews, documentation, literature study, internet searching. The data analysis technique was carried out through four paths, namely data reduction, data presentation, data validity test and conclusion drawing.The results show that in the perspective of management accountants and public accountants, earnings management practices cannot be viewed as earnings manipulation as long as these practices are carried out within the framework of accounting standards. They also argue that earnings management is not said to be corrupt behavior, unless the practice is not carried out in accordance with accounting standards. While the views of investment advisors and tax inspectors, the practice of accounting standards carried out with any pattern and strategy is a reflection of corrupt behavior because of a corrupted mind. They argue that earnings management practices are always carried out systematically based on certain motivations and interests. Earnings management is a practice that is of no value to the company's stakeholders so this practice should be avoided. Viewed from the perspective of ati mapping that earnings management can be seen from the good or bad intentions of a manager in carrying out his practice, motivation or interests that are detrimental to other parties, it can be said that the practice of earnings management is an act of fraud that can be categorized as a corrupted line of thought.